Substance use among pregnant women: frequency and effects - İzci, Filiz; Bilici, Rabia (Journal of Dependence, 2015)
Substance use is one of the growing problems all over the world. Psychiatric disorders associated with substance use and devastating effects of it on society have an impact on the whole community regardless of race, gender or region. Until recently, substance use was thought to be more frequent among men; more recent studies have shown that the difference of substance use levels between men and women was gradually reducing. Also, substance use has been shown to have a more different and destructive effect on women compared to men. Taking into account the women’s motherhood and fertility properties, social destructive effects of substance use and possible intrauterine growth and neurode-velopmental problems during childhood and beyond should not be overlooked. Here we aimed to review substance use problems and frequency among pregnant women in accordance with literature, emphasize that substance use can affect whole society causing problems on women’s health, maternal and infant health and evaluate the frequency in our country and around the world.
Keywords: Pregnant; substance; frequency; effect